Empire of Sand The Seri Indians and the Struggle for Spanish Sonora, 1645-1803 - Sheridan, Thomas E. (University of Arizona Press, 2021)
From the earliest days of their empire in the New World, the Spanish sought to gain control of the native peoples and lands of what is now Sonora. While missionaries were successful in pacifying many Indians, the Seris-independent groups of hunter-gatherers who lived on the desert shores and islands of the Gulf of California-steadfastly defied Spanish efforts to subjugate them. Empire of Sand is a documentary history of Spanish attempts to convert, control, and ultimately annihilate the Seris. These papers of religious, military, and government officials attest to the Seris' resilience in the face of numerous Spanish attempts to conquer them and remove them from their lands. The documents include early observations of the Seris by Jesuit missionaries, descriptions of the collapse of the Seri mission system in 1748, accounts of the invasion of Tiburón Island in 1750 and the Sonora Expedition of 1767-71, and reports of late eighteenth-century Seri hostilities. Thomas E. Sheridan's introduction puts the documents in perspective, while his notes objectively clarify their significance. By skillfully weaving the documents into a coherent narrative of Spanish-Seri interaction, he has produced a compelling account of empire and resistance that speaks to anthropologists, historians, and all readers who take heart in stories of resistance to oppression.